New Sight: Enzymes as Targets for Drug Development - Sung-Kun Kim (Current Issues in Molecular Biology, 2023)
In the dynamic realm of medical research, a resounding chord is struck by recent studies that have propelled drug discovery to new horizons across a spectrum of disciplines [...]